Unraveling IFI44L’s biofunction in human disease - Du, Juan; Luo, Hui; Ye, Shuang; Zhang, Hui; Zheng, Zhen; Liu, Kaitai (Frontiers in Oncology, 2024)
Interferon-induced protein 44-like (IFI44L) is regarded as an immune-related gene and is a member of interferon-stimulated genes (ISGs). They participate in network transduction, and its own epigenetic modifications, apoptosis, cell-matrix formation, and many other pathways in tumors, autoimmune diseases, and viral infections. The current review provides a comprehensive overview of the onset and biological mechanisms of IFI44L and its potential clinical applications in malignant tumors and non-neoplastic diseases.